Liftoff of Propane - Air Diffusion Flames By Axis Symmetric Co-flow Air Injection - I Made K Dhiputra; Harinaldi Harinaldi; NK Caturwati; Dimitri Rulianto (Testing Center for Oil and Gas LEMIGAS, 2009)
Combustion of gas with diffusion system is widely used in many residential gas appliances like stove, engine furnaces and industrial furnaces. Phenomenon of lifted flame is often happened at diffusion flame where the stream of fuel and air into combustor flow separately. Hence the combustion process needs time so that mixing of air and fuel reach the condition ready for burnt. This condition make the burner tip protected from high thermal load and more safe to operate. In this paper, propane was ejected into quiescence air through nozzle having 1.8 mm holes diameter. Fuel flow rate was increased until liftoff conditions exceed; hereinafter flow rate of fuel was made constant at 69 ml/s and air was ejected around of fuel with axis symmetric flow. Liftoff behavior of diffusion flames was investigated for various air flow rate: 17.9 ml/s – 89.9 ml/s. Lifted distance decreased from 130 mm to 90 mm when air was injected with flow rate of 19.1 ml/s, however, it increased to 100 mm when air flow rate increased to 35.9 ml/s. Cold-flow simulation showed the moderate air flow rate give a faster density degradation at axial line compared to larger air flow rate. It means moderate flow rate of air support a better air-fuel mixing than faster one.